DA'WAH MODALITIES IN THE MILLENNIAL ERA; MEASURING COMPETENCE AND MILITANCY - Moh. Toriqul Chaer; Asnan Purba; Misno (IJGIE (International Journal of Graduate of Islamic Education), 2022)
Da'wah is the duty of all Muslims in whatever capacity they are, as the saying goes: We are Dai before everything else. So important is this da'wah that it must be carried out with trust and integrity so that the goals and targets of this da'wah are conveyed professionally and proportionally. The rapid and dynamic development of technology and changing times requires that each of us as preachers have adequate competence with high militancy in order to have a domino effect on all elements of society in this millennial era, where their characters and paradigms are very different from the previous era. Very rapid progress in this very modern industrial technology era, coupled with a global pandemic situation that forces every generation to be friendly and adapt to the current digital world and social media. To achieve these goals and targets and needs, it is very important that every preacher has adequate competence and high militancy, of course, by providing education or training both informally and informally so that they can contribute significantly and effectively in the world of da'wah in this millennial era.